Cyanidin attenuates IL-17A cytokine signaling mediated monocyte migration and differentiation into mature osteoclasts in rheumatoid arthritis. (June 2021) - Samarpita, Snigdha; Rasool, Mahaboobkhan
Highlights: Cyanidin, a potent inhibitor of IL-17 signaling associated pathogenesis in RA. Cyanidin modulates IL-17A/IL-17RA interaction. Cyanidin blocks IL-17A/p38 MAPK signaling mediated monocyte migration. Cyanidin suppresses osteoclastogenesis via regulating RANKL and OPG expression. Abstract: Interleukin (IL)-17A signaling pathway plays a critical role in the initiation and progression of rheumatoid arthritis (RA) and represents a viable target for RA therapy. Cyanidin, a flavonoid compound, is a novel inhibitor of IL-17A/IL-17RA (receptor subunit A) interaction in several inflammatory diseases. However, the therapeutic efficacy of cyanidin on IL-17A cytokine signaling induced monocyte migration and fibroblast-like synoviocytes (FLS) released RANKL mediated osteoclastogenesis in RA has not yet been deciphered. In the present study, cyanidin impeded IL-17A induced migration of monocytes isolated from adjuvant-induced arthritic (AA) rats. At the molecular level, cyanidin blocked the activation of p38MAPK signaling in response to IL-17A. Importantly, cyanidin downregulated IL-17A induced expression of HSP27, CXCR4, and CCR7 in AA monocytes via modulating IL-17/p38 MAPK signaling axis. Alternatively, cyanidin significantly suppressed the formation of matured osteoclasts and bone resorption in a coculture system consisting of IL‐17 treated AA‐FLS and rat bone marrow-derived monocytes/macrophages. Further, cyanidin significantly inhibited the expression of RANKL and increased the expression of OPG in AA-FLS via blunted activation of IL-17A/STAT-3 signaling cascade. Interestingly, cyanidin impaired IL-17A induced overexpression of IL-17RA. Taken together, our study proposes a novel therapeutic function of cyanidin towards targeted inhibition of IL-17A/IL-17RA signaling mediated disease severity and bone erosion in RA.